Occurrence and identification of aphid (Hemiptera: Aphididae) species on several host plants in the main campus of Hasanuddin University, Makassar - Rahmat Rahmat; M. Takwa; Athiyyah Salsabilla Lalisu; A. M. Bintang Ramadhan Galigo; Wardani Syahrani; Ravindra Chandra Joshi; Ito Fernando; Ahwiyah Ekawaty Said; Yani Maharani; M. Bayu Mario (Department of Plant Pest and Diseases, Faculty of Agriculture, Hasanuddin University, 2026)
Aphids (Hemiptera: Aphididae) are important agricultural pests that damage host plants and transmit plant viruses. A qualitative survey was conducted from March to May 2026 across various zones of the Hasanuddin University campus, Makassar, Indonesia to document aphid occurrence and host associations. Aphid colonies were collected purposively from agricultural crops, ornamental plants, and weeds, and species identification was performed through microscopic examination of diagnostic morphological characters. Only one species, Aphis gossypii Glover, was identified from the collected aphid colonies. This species was associated with Capsicum annuum, C. frutescens, Melothria pendula, and Ficus benjamina. These observations provide baseline information on the occurrence and host associations of A. gossypii within the campus environment and highlight the potential role of weeds and ornamental plants as alternative hosts supporting aphid persistence. The present inventory provides preliminary information for future monitoring and integrated pest management studies.